Implementasi Akad Murabahah Dalam Perbankan Syariah di Indonesia - Muhammad Alfan Rumasukun; Muhammad Ghozali (Islamic Economics Journal, 2016)
The term “Murabahah” refers to contracts in which a financial institution purchases goods upon the request of a client, who makes deferred payments that cover costs and agreed-upon profit margin for the financial institution. The financial institution handles payment to a supplier and the incidental expenses of delivery (against a deferred payment made by the buyer to cover delivery costs and agreed-upon share of the buyer’s mark-up). Murabahah is the most widely used instrument of Islamic banking with seventy-five percent of total contract being murabahah based. It is widely used in consumer and corporate financing as well as in subordinated or term financing. The aim of this article is to review and analyze the murabahah contract, the most important investment mechanism in Islamic banking today both in its theoretical and practical aspects.